Communication of Mental and Historical Development (Bintaljarah) in Religious Moderation at Makodam XIV/Hasanuddin - Hasriani, Andi; Muhammad, Firdaus; Tajibu, Kamaluddin; Tike, Arfuddin; Paduppai, Andi (Lembaga Sembilan Tiga Community, 2025)
This study explores the strategic role of Da'wah communication within the Mental and Historical Development Unit (Bintaljarah) of Kodam XIV Hasanuddin in fostering religious moderation among soldiers. Using a qualitative-descriptive approach with a communication science perspective, this research identifies five core pillars of the propagated message: national commitment, tolerance, non-violence, accommodative stance toward local wisdom, and exemplary leadership (Uswah Hasanah). The findings reveal that the communication process is systematically structured through planning, message encoding, media selection, and evaluation. Furthermore, Bintaljarah functions as a vital agent for de-radicalization and a stabilizer of institutional identity. This study implies that integrating religious moderation into military mental development is crucial for maintaining national integrity in a multicultural society